Role of Islamic financial institutions in addressing financial exclusion: a methodological mix approach - Muhammad, Tijjani; Al-Shaghdari, Fahd Mohammed Obad; Ngah, Besar (Akademi Zakat, Pusat Pungutan Zakat (PPZ-MAIWP), 2023)
This paper elucidates the mediating role of Islamic Financial Institutions in addressing financial exclusion in northern Nigeria, using poverty, awareness, religiosity, and attitude toward government policy as explanatory factors. The study employed a random sampling of 450 respondents using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) was used for data analysis. The secondary data were generated from Nigerian Security Exchange Commission under Islamic Finance Development Indicator. The study identified some theoretical and managerial contributions. The research indicates a highly effective mediation of Islamic financial institutions’ performance in addressing financial exclusion in northern Nigeria. The study also contributed significantly to the literature by using the mediating variable to address financial exclusion. The present study developed an integrated model which defines financial exclusion and its approach through the mediation role of Islamic financial institutions in addressing the financial exclusion and poverty reduction in northern Nigeria.